PENGARUH METODE PEMBELAJARAN KONTEKSTUAL TERHADAP HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 105383 PERTUMBUKAN PADA MATERI POKOK SIFAT BENDA DAN PERUBAHAN - Kurnia Lestari; Vivi Uvaira Hasibuan (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2022)
The purpose of this research The Influence of Contextual Learning Methode on The Learning Outcomes of grade IV Students at SD Negeri 105383 Pertumbukan on the subject matter of the nature of things and changes. In this research, the method used is a quasi-experimental design with nonequivalent control. The research was conducted at SD Negeri 105383 Pertumbukan, from oktober to nopember 2021. The research was conducted at class IV-C (using Contextual Learning Methode through Cooperative Learning) and class IV-D (using conventional model). The selection of these two classes was based on purposive sampling technique The instrument used is an objective test in the form of multiple choice questions that have been tested for validity and reliability as many as 15 items. In this research, The data analysis technique used is the Liliefors test for normality test, Bartlett test for homogeneity test and t test (t-test) for two-party hypothesis testing. Based on the results of data analysis, it was found that there was a significant effect The Influence of Contextual Learning Methode on The Learning Outcomes of grade IV Students at SD Negeri 105383 Pertumbukan on the subject matter of the nature of things and changes. This conclusion is based on the results of the two-party hypothesis test on the posttest results of the two classes. The results obtained are the t count value is 13.07 and the t table at the 5% significance level is 1,67. It can be seen that the value that t count > t table or 13.07 > 1.67 means accept Ha, reject Ho.